The effect of modulating platelet reactive oxygen species by the addition of antioxidants to prevent clearance of cold-stored platelets - Rufeng Xie; Yiming Yang; Xueyu Jiang; Li Gao; Juan Sun; Jie Yang (Hematology, Transfusion and Cell Therapy)
Background: It is known that the rapid clearance of cold-stored platelets is attributed to various storage lesions, including an abnormal increase in reactive oxygen species when platelets are exposed to cold temperatures. As an antioxidant, N-acetylcysteine exhibits some significant effects on scavenging various reactive oxygen species and inhibiting cell damage and apoptosis. Aims: This study aimed to investigate the effects of N-acetylcysteine on reducing reactive oxygen species production and protecting cold-stored platelets from phagocytosis and clearance, and to determine the optimal concentration of N-acetylcysteine. Methods: Platelet concentrates were divided into three groups: room-temperature-stored platelets, cold-stored platelets, and cold-stored platelets with the addition of different concentrations of N-acetylcysteine. After five days of storage, reactive oxygen species production, lipid peroxidation levels, activation marker expressions, GPIb/ɑ desialylation with exposure of glycan residues and other quality parameters of platelets were measured and compared between the groups. Phagocytosis of platelets was detected by phorbol 12-myristate 13-acetate-activated THP-1 or Hep G2 cells. Moreover, the recovery of infused platelets was measured in severe combined immunodeficient mice at different timepoints. Results: After 5 days of storage, cytoplasmic reactive oxygen species significantly increased in chilled compared to non-chilled platelets; they were notably reduced with the addition of N-acetylcysteine, particularly at a concentration of 5 mM. Compared with chilled platelets, the P-selectin and phosphatidylserine expressions, as well as exposure of GPIb/ɑ glycan residues, were significantly reduced with 5 mM of N-acetylcysteine. Phagocytosis of platelets by THP-1 or Hep G2 cells was significantly lower in 5 mM of N-acetylcysteine compared to cold-stored platelets without N-acetylcysteine. Conclusions: This study demonstrated correlations between reactive oxygen species production and their pro-oxidant effects on platelet clearance after cold storage. The addition of N-acetylcysteine at an appropriate concentration do not only protects chilled platelets from storage lesions caused by reactive oxygen species overproduction but also prevents platelet phagocytosis in vitro and clearance in vivo, thereby extending circulating time.